The effectiveness of Federal Agricultural Marketing Authority (FAMA) as a marketing channel in distributing private brand products named Agromas (a case study of FAMA Seremban) / Hamidah Lokman - Lokman, Hamidah (Faculty of Business and Management, 2005)
Marketing Channel means distribution. The distribution system covers the whole range of operations and movement of goods between the producers and the consumers. Distribution contributes no profit to a company; however without satisfactory distribution there is unlikely to be an income from sales. In order to be an effective marketing channel, distribution must be viewed as a whole before it can be recognized into specific duties which can be fitted into a management structure that will help to determine their true relationship. In this research, an investigation towards FAMA as marketing channel in distributing AgroMas products has been conducted. The objective of the study are: (1) To identify the effectiveness of FAMA in distributing private brand AgroMas products, (2) To identify whether FAMA widely distributes its AgroMas brand products accurately, and (3) To identify level of customer awareness towards AgroMas brand. The output from questionnaires had been conducted helps in find main variables that effect FAMA channel distribution. Results indicate that prompt service and advertising does play an important role to make sure products be known and thus creates demand.